Inhibition of Cracks on the Surface of Cement Mortar Using Estabragh Fibers - Tahereh Soleimani; Ali Akbar Merati; Masoud Latifi; Ali Akbar Ramezanianpor (Advances in Materials Science and Engineering)
The influence of adding Estabragh fibers into the cement composites of mortar on surface cracks and mechanical properties of mortar has been studied at various fiber proportions of 0.25%, 0.5%, and 0.75%. The mortar shrinkage was evaluated by counting the number of cracks and measuring the width of cracks on the surface of mortar specimens. Although the Estabragh fibers loss their strength in an alkali environment of cement composites, the ability of Estabragh fibers to bridge on the microcracks in the mortar matrix causes a decrease in the number of cracks and in their width on the surface of the mortar samples in comparison with the plain mortar. However, considering the mechanical properties of specimens such as bending strength and compressive strength, among all fiber proportions, only the specimens with 0.25% of Estabragh fiber performed better in all respects compared to the physical and mechanical properties of reinforced cement composite of mortar. Consequently, by adding 0.25% of Estabragh fibers to the cement mortar, a remarkable inhibition in crack generation on fiber-containing cement composite of mortar is achieved.